Implementasi Integrasi Nasional Ditinjau dari Nilai-Nilai Kewarganegaraan dalam Upaya Mewujudkan Kesejahteraan Mahasiswa Prodi PGSD Universitas PGRI Adi Buana Surabaya - Nurul Maulidah; Angella Rahma Aprilia; Laeticia Najma Widodo; Irma Fatmawati; Nabilla Azizah; Cecilia Natasya Putri; Karina Avanda Fitri; Diah Kurnai Sari; Diva Ayu Wulandari; Luthfia Azizah; Novi Yosa Aidil Ramdhani; Suyono Suyono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research was conducted to find out how much National Integration is implemented in terms of civic values in an effort to realize the welfare of PGSD study program students at PGRI Adi Buana University, Surabaya. The importance of citizenship for PGSD study program students at PGRI Adi Buana University, Surabaya so that they have a strong grip on avoiding and solving national problems. This will support students to have basic competencies, namely becoming scientists who have a sense of nationality and love of the country, are civilized democracies, become citizens who are competitive, disciplined, and actively participate in building a peaceful life based on civic values. students as the nation's next generation of young people to provide national values and a comprehensive understanding of the archipelago, national resilience, rights and obligations as citizens, democracy, the constitution and human rights in facing challenges.